Which Is the Ideal Treatment for Benign Diffuse and Multinodular Non-Toxic Goiters? - Knobel, Meyer (Frontiers in Endocrinology, 2016)
Patients with large benign goiters often present local compressive symptoms that require surgical treatment, including dysphagia, neck tightness, and airway obstruction. In contrast, patients with such goiters who remain asymptomatic may be observed after exclusion of malignancy. The use of levothyroxine (LT4) to reduce the volume of the goiter is still a controversial treatment for large goiters, and the optimal surgical procedure for multinodular goiter is still debatable. Radioiodine is a safe and effective treatment option when used alone or in combination with recombinant human TSH. This review discusses current therapeutic options to treat diffuse and multinodular non-toxic benign goiters.